Dealing with donor issues in therapeutic cell donation. (31st May 2013) - Buser, A.; Halter, J.
<x xml:space="preserve">Abstract</x> The number of allogeneic stem cell transplantations increases annually and hence does the need for therapeutic cell donations in parallel. These donation procedures harbour immediate, short‐term and late adverse reactions. Most of these events are mild to moderate; however, fatalities have been reported. Avoiding as many adverse events as possible is paramount. Donor follow up as proposed by the Worldwide Network for Blood and Marrow Transplantation and the development of donor eligibility criteria for all donors are important measures to better understand the risk of therapeutic cell donation and to increase donor safety.